Pengaruh Social Media Marketing dan Brand Image terhadap Minat Pembelian Generasi Z pada Miniso di Kota Singaraja - Krisna Putra, I Nyoman; Sayang Telegawathi, Ni Luh Wayan (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
ABSTRACT The rapid growth of the retail industry in Indonesia has intensified competition, including for Miniso in Singaraja, which faces challenges in increasing Generation Z’s purchase intention despite having a positive brand image. The gap between favorable brand perception and low purchase intention indicates the importance of social media marketing strategies and brand image in driving consumer purchase intention. The purpose of this study is to examine the relationship between social media marketing and brand image on Generation Z’s purchase intention. This study employs a quantitative approach using multiple linear regression analysis. The results show that social media marketing and brand image partially and simultaneously have a positive and significant effect on Generation Z’s purchase intention. This study confirms that optimizing social media marketing and strengthening brand image are effective strategies for Miniso in Singaraja to increase Generation Z’s purchase intention. Keywords: Purchase Intention, Social Media Marketing, Brand Image